KEMAMPUAN MENANGGAPI PEMBACAAN CERPEN SISWA KELAS VII SMP NEGERI 3 LINGGO SARI BAGANTI KABUPATEN PESISIR SELATAN MENGGUNAKAN MEDIA AUDIO VISUAL - Monika, Astri; Eska, Wirnita; Afrinda, Putri Dian (Pendidikan Bahasa Indonesia, 2014)
This research is motivated by the students self-confidence yet to respond to the reading of short stories , teachers tend to use the lecture method. The purpose of the study to describe the ability to respond to the reading of short stories class VII students of SMP Negeri 3 Linggo Sari Baganti using audiovisual media . Type a descriptive quantitative research methods. The study population was a class VII student of SMP Negeri 3 Linggo Sari Baganti.Teknik sampling Purposional Random Sampling. Instrumen is test.Â  Research data analysis,, it was concluded that the ability to respond to reading short stories class VII students of SMP Negeri 3 Linggo Sari Baganti using audio media visual more than enough with an average 77.77 % of students. Responsiveness to reading short stories class VII students of SMP Negeri 3 Linggo Sari Baganti using audio-visual media indicator 1 (pronunciation) is more than adequate with an average 73.33 %, indicator 2 (intonation) is more than adequate with an average 75.55 %, indicator 3 (expression) is the average of 57.77 % .Indicator 4 (attitude) is quite good with an average of 84.44%, indicator 5 (content short stories) splendidly with 94.44 % average rats.